Presentation of a Causal Model of Campus Community Quality, Knowledge Sharing and Academic Performance among Students of Shiraz University of Medical Sciences - Rahmatollah Marzooghi; Mehdi Mohammadi; Fahimeh Keshavarzi (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: As an intellectual and ethical environment, university campus increases motivation and enhances constructive interactions among students by creating and disseminating knowledge and leads to emergence of talents. The purpose of this study was to examine the relationship among university Campus community quality, knowledge sharing and students’ academic performance. Methods: This descriptive-correlational study was performed on all students of Shiraz University of Medical Sciences in 2013-14 academic years. 175 students were selected through random sampling method. Research tools were the College and University Community Inventory Ernest Boyer and the knowledge sharing behavior scale derived from the work of Van den Hooff and De Ridder cited in Salimi. The questionnaires were distributed among subjects after calculating the validity and reliability. Data were analyzed through simultaneous multiple regression analysis according to Baron and Kenny’s model. Results: Results showed that: 1) Campus community quality was a significant positive anticipant of students’ academic performance (p<0.0001T f=50.83). 2) Campus community quality anticipated 61% of students’ total knowledge sharing variance. 3) Campus community quality components had a significant influence on knowledge reception (p<0.0001, f=33.134). 4) Campus community quality anticipated 76% of students’ total knowledge reception variance. 5) Knowledge sharing and Campus community quality components had significant effects on students’ academic performance (p<0.0001, f=76.74). 6) Due to the mediating role of knowledge sharing, Campus community quality also was a significant positive anticipant of students’ academic performance. Conclusion: According to the results, in order to enhance and promote campus community quality and students’ knowledge sharing, the following are suggested: improving the quality of campus community in line with target-orientation, promoting scientific and ethical relations among the members, maintaining respect for students and enhancing university physical facilities, and encouraging students participation in knowledge sharing.